Medical imaging research in Malaysia - Nurul Husna binti Kamarudin (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2019)
The concept of evidence based practice is to enable medical imaging practitioners (radiographers and academicians) to deliver optimal health care services. Research is an important tool to enhance the growth of the discipline. This study explored the state of medical imaging research in Malaysia. To achieve the aim, the global trend of research was examined using Web of Science (WoS) and Scopus online databases. The bibliometric and thematic analysis explored the theme and sub-themes of research in medical imaging, as well as the collaboration activities in research and contributions of Malaysia based researchers in medical imaging research. The findings found that the major theme and sub-theme of the global trend of research in medical imaging was clinical-modality comparison. The professional background for the authors are mostly from university-based researchers. The collaboration activities in research was encouraging and the contribution of Malaysia based researchers was not satisfactory. A questionnaire study was done among medical imaging practitioners that explored the research state among medical imaging practitioners. It examined among others the research obstacles and preferences among. There was significant difference in terms of knowledge, attitude and practice among medical imaging practitioners in research. The main research obstacles outlined by medical imaging practitioners was insufficient time. Their research preferences in medical imaging was the safety aspect; radiation safety, modality safety, cross infection. Based on the findings, a conceptual framework to enhance the state of research in medical imaging was proposed. There is the need of alignment in research among medical imaging practitioners in order to enhance the state of research in medical imaging Malaysia. This can be achieved through the setting up of a research centre. Among others the research centre is expected to centralize the research activities among medical imaging researchers and to align the research activities within the needs of Malaysian population and aspiration of government. More researches that are relevant to local practices and needs are needed especially from Malaysian researchers. For future research involvement, it suggested that more collaboration between academicians and service providers in research in medical imaging is needed to strengthen the contribution of research to meet the needs of patients. This finding can be very helpful for future researchers to find out the most needed topic to conduct a research that could benefit the medical imaging services. This can help to strengthen the medical imaging practice as well as to increase home-grown research.